مهارة الكلام : تاريخها وكيف نتعلمها ونعلمها - ahmad tabrani (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2019)
AbstractThe purpose of this study are to discover the history of speech skills and how to learn and teach them. Students who study Arabic, especially in speech skills, face the problems and difficulties they seek to address. Teachers also do not have a successful teaching ability.The results of the study are the history of speech skill associated with the emergence of the language, which is divided into three theories: the theory of inspiration and revelation, simulations of natural voices, the theory of agreement and moderation and terminology. And how to learn and teach the skill of speech is to save dialogue and training, and encourage students to speak, and practice Arabic speech, the way of dialogue, and corrected oral errors.